PENGARUH LATIHAN LATERAL CONE HOPS TERHADAP POWER OTOT TUNGKAI PADA PEMAIN BULUTANGKIS MAN 1 PEKANBARU - Firdaus, Aji Panca; Zainur, Zainur; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine whether there is an effect of lateral cone hop training on leg muscle strength in badminton players at MAN 1 Pekanbaru. The purpose of giving lateral cone hop training is to increase the leg muscle strength of badminton players MAN 1 Pekanbaru. The basis of this exercise is based on the results of observations on the MAN 1 Pekanbaru badminton players in the field, it is known that there are many training deficits that lead to greater power, in this case the power of leg muscle. In this study, the authors concentrate on only one form of exercise, namely Lateral Cone Hops training, because according to MAN trainers 1 form of this exercise has never been tried in the badminton game MAN 1 Pekanbaru. After being formulated and limited, the purpose of this study is to determine whether there is an effect of lateral cone hop training on the leg muscle strength of the badminton players of MAN 1 Pekanbaru. The research design was a pre-test post-test one group design that was started by doing a pre-test vertical jump to see if there was an improvement after doing lateral cone hop training on leg muscle in badminton. Based on the analysis of the t-test, the total was 8.27 and Ltabel was 1.895. Means Thitung> TTable. And based on statistical data analysis, there is an average pre-test of 42.87 and an average post-test of 49.75. Based on the findings and data processing above, it can be concluded as follows: That is, lateral cone hop (X) exercises affect leg muscle strength (Y) in badminton players MAN 1 Pekanbaru.Key Words: Lateral Cone Hope Training Against Muscle Power